Reformulating Russia : the Cultural and Intellectual Historiography of Russian First-Wave Émigré Writers - Mjør, Kåre Johan (Russian history and culture (Leiden, Netherlands), 2011)
G.P. Fedotov, G.V. Florovskii, N.A. Berdiaev, V.V. Zen'kovskii, historiography, migr literature, philosophy, theology, narrative analyses.